Evaluation of glass nano/microstructures replication fidelity after laser-assisted hot embossing process - Lee, May Shian Helen (2023)
Micro/nanostructured glass allows the realization of many optical devices potentially exploited in numerous applications, such as in the field of imaging, point-of-care testing (POCT) for medical diagnostics, bio-inspired surfaces, and biosensors. Hot embossing is a simple, low-cost and efficient method for fabricating glass micro/nanostructures. Nevertheless, the existing hot embossing process suffers from a long thermal cycle, poor replication fidelity, especially for sub-micron features, and excessive glass thickness reduction. To date, it is still challenging to fabricate glass-based micro/nanodevices of high quality efficiently by using conventional hot embossing. To improve the process, the application of an external source to supplement the hot embossing process, such as ultrasonic, electrical, or laser-assisted means is gaining interest. Despite the potentials of laser-assisted hot embossing as a direct, rapid, and large area patterning method, its realization for practical application is still challenging. Various parameters need to be considered during the laser-assisted hot embossing process, including laser energy density, laser scanning speed, imprinting load and preheating temperature. This study proposed a laser-assisted hot embossing method that enables rapid imprinting of various micro and nanoscale patterns on K-PG375 optical glass substrates, with a shorter overall thermal cycle. The effect of laser-assisted scanning hot embossing parameters on the embossed glass pattern width, height and shape was investigated. Furthermore, the effects of mold pattern aspect ratio on the replication height of the embossed glass was analyzed. This method utilized the synergy of silicon mold high transmittance and strong optical absorption of glass at wavelength of 10.6 μm. The glass absorbed photon energy provided substantial heating of the glass surfaces, thus reducing the glass surface viscosity and accelerating the glass material filling in micro/nanostructure mold cavities. The results revealed that by controlling related parameters, such as laser scanning speed, preheating temperature, and pressing load, various high-resolution periodic grating, hole, and pillar patterns can be obtained. Pattern width ranging from 225 nm up to 50 μm, was successfully copied to the glass surface with a very short contact pressing time, instantaneously after each laser pass. Pattern transfer occurred when the scanning speed varied between 5 mm/s and 25 mm/s, preheating temperature in the range of 320℃ to 335℃ and moderate load in the range of 0.2 MPa to 0.5 MPa. It was found that the filling ratio improved as the scanning speed decreased. At a scanning speed of 30 mm/s, the replication failed due to insufficient temperature rise at the glass surface. When the scanning speed was reduced to 1 mm/s, several problems such as excessive deformation in the bulk glass and strong stiction of glass to the mold after demolding or glass cracking was observed. It was clearly observed that, as the aspect ratio increased, the average replication height of embossed glass decreased. As proof of concept, the optical performance of fabricated glass as diffractive optical elements and optical filter for guided mode resonant was also demonstrated. The measured diffractive grating spacing and order after illuminated by laser source were in good agreement with the theoretical calculation. In the latter, the utility of laser-assisted, imprinted glass nanostructures as guided mode resonant (GMR) optical filter was evaluated. The peak spectral values obtained were satisfactory, which yielded an average full width at half maximum (FWHM) and peak wavelength value (PWV) of 4.6 nm and 691.39 nm, respectively. Overall, the proposed method enabled a simple, low-cost, high-throughput approach for the fabrication of fine patterns on glass for various optical applications.